Novel scanning probe microscope instrumentation with applications in nanotechnology - Humphry, Martin James (2000)
A versatile scanning probe microscope controller has been constructed. Its suitability for the control of a range of different scanning probe microscope heads has been demonstrated. These include an ultra high vacuum scanning tunnelling microscope, with which atomic resolution images of Si surfaces was obtained, a custom-built atomic force microscope, and a custom-built photon emission scanning tunnelling microscope. The controller has been designed specifically to facilitate data acquisition during molecular manipulation experiments.